Challenges and Opportunities: A Phenomenological Analysis of Blind Passengers' Train Travel Experiences in Indonesia - Hendyansyah Putra; Innocentius Bernarto; Rudy Pramono (Jurnal Entrepreneur dan Entrepreneurship, 2024)
This research aims at the experiences of blind passengers using long-distance intercity trains. Although prior research has been done on transportation use by blind consumers, their customer experience in Indonesia has yet to be thoroughly examined. This method of this study employs Smith's Interpretative Phenomenology Analysis (IPA) method, conducting video conference interviews with six blind passengers who frequently travel on long-distance intercity trains. These in-depth interviews were analyzed using double hermeneutics to develop the Blind Passenger Journey Mapping (BPJM) and Blind Passenger Journey & Experience (BPJE) models. The results reveal that blind passengers often require assistance at nearly all touchpoints and need more accessible services throughout their journey. Two main themes emerged: Blind Passenger Experience (BPE) and Sighted Mobility Oriented Assistant (SMOA). The paper identifies significant gaps and opportunities in the current service design for blind passengers, suggesting that addressing these through entrepreneurial initiatives cannot only improve inclusivity and accessibility but also revolutionize the travel industry by opening a potentially underserved market, promoting a more equitable and sustainable travel ecosystem.